Effect of Early Feed Restriction on Performance Characteristics and Serum Thyroxin of Broiler Chickens - Hassanabadi, A.; Moghaddam, H. Nassiri (International Journal of Poultry Science, 2006)
An experiment was conducted to evaluate the effect of early feed restriction on performance characteristics and serum thyroxin of broiler chickens. The experiment was designed in a 2 x 2 factorial with 5 replicates of floor pens with 12 male or female chicks in each. 240 male and/or female day-old chicks were weighted and randomly allocated to two treatment groups of each sex. Two treatments involved, control group and restricted group, which were fed a mixture of 50:50 rice hulls and commercial starter diet with supplementation of trace minerals and vitamin premixes from 4 to 11 days of age. All groups were fed the same starter, grower and finisher diets from 11 to 56 days of age. Live body weight of restricted birds was compensated on day 42 of age and was numerically more than restricted group at 49 and 56 days of age. Daily feed intake up to 42, 49 and 56 days of age wasn`t affected by treatments. Feed efficiency in the restricted birds was significantly (p< 0.05) better than of control birds up to 56 days of age. Among the body composition, only carcass fat content of restricted birds was significantly (p< 0.05) lower than of control birds. Abdominal fat pad percent of restricted birds at 49 and 56 days of age was significantly (p< 0.05) lower than of control birds. T4 concentration on day 11 in restricted group was significantly (p< 0.05) lower than control group. Its concentration during accelerated growth period was not significantly (p>0.05) more than control group.